Adoption and Utilization of E-Learning Platform Facilities in Higher Education: A Study of the Institut Catholique de Kabgayi (ICK), Rwanda - Jean Paul Ndayizigiye (Academic Bright Collaboration, 2026)
E-learning has become an integral part of higher education worldwide, offering new opportunities for flexible, accessible, and student-centered learning. In Sub-Saharan Africa, however, the pace of adoption has been uneven, often constrained by infrastructural and pedagogical challenges. This study investigates the adoption and use of e-learning platforms at the Institut Catholique de Kabgayi (ICK) in Rwanda, with particular attention to institutional readiness, infrastructure, and the perceptions of lecturers and students. Using a mixed-methods design, data were collected from lecturers, administrators, IT staff, and students to assess preparedness, barriers, and opportunities in digital learning. The findings reveal that while ICK has invested in establishing an e-learning platform, its effective use remains limited due to inadequate infrastructure, insufficient training, unstable internet connectivity, and varying attitudes toward online education. Nevertheless, participants acknowledged the potential of e-learning to enhance teaching effectiveness, promote flexibility, and increase access to higher education. The study contributes to the literature by highlighting the specific challenges and opportunities of e-learning adoption in a Rwandan context and offers practical recommendations for policymakers and institutional leaders seeking to strengthen technology-enhanced learning in developing countries.